2015
DOI: 10.1074/jbc.m115.675124
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Pleckstrin Homology Domain-containing Protein CKIP-1 in Activation of p21-activated Kinase 1 (PAK1)

Abstract: Background: PAK1 is phosphorylated and activated by the protein kinase CK2 in response to EGF. Results: Upon EGF stimulation, CKIP-1 recruits CK2 to PAK1 in membrane ruffles in a PI3K-dependent manner. Conclusion: PI3K activates PAK1 at the plasma membrane by promoting CK2 phosphorylation of PAK1 via CKIP-1. Significance: This is the first evidence of spatial regulation of PAK1 activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…Finally, we assessed whether PAKs may be activated by noradrenaline, endothelins, or dihydrotestosterone in WPMY-1 cells. Activation of group I PAKs includes phosphorylation at common positions, which may be investigated using phospho-specific antibodies [ 35 37 ]. Stimulation of WPMY-1 cells with endothelin-1 (3 μM) for 10 or 20 min increased the content of phosphorylated group I PAKs (i. e., PAK1-3), while the content of PAK1 and β-actin was similar in stimulated and control cells ( Fig 8 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, we assessed whether PAKs may be activated by noradrenaline, endothelins, or dihydrotestosterone in WPMY-1 cells. Activation of group I PAKs includes phosphorylation at common positions, which may be investigated using phospho-specific antibodies [ 35 37 ]. Stimulation of WPMY-1 cells with endothelin-1 (3 μM) for 10 or 20 min increased the content of phosphorylated group I PAKs (i. e., PAK1-3), while the content of PAK1 and β-actin was similar in stimulated and control cells ( Fig 8 ).…”
Section: Resultsmentioning
confidence: 99%
“…Our findings with PAK inhibitors in WPMY-1 cells are in line with previous observations. Thus, a critical role of PAKs for actin organization, including polymerization and its organization to filaments, as well as a role for actin-dependent functions such as migration, morphology, proliferation, or contraction was observed in various cell types [ 35 , 44 47 , 72 ]. Deorganization of actin filaments, going along with depolymerization, shortening of filaments, and alterations in morphology can be seen in our phalloidin stainings of WPMY-1 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the first report of p41ARC serving as a downstream effector of PAK1 signaling in skeletal muscle cells. PAK1 has been shown to phosphorylate p41ARC in vitro, in MCF-7 cancer cells upon EGF stimulation (24,26), and in melanoma cells (25). p41ARC is one of two principle ARP2/3 subunits, the other and more commonly used subunit being ARPC1A (40).…”
Section: Cytoskeletal Regulation Of Skeletal Muscle Glucose Uptakementioning
confidence: 99%
“…25 It was reported that CKIP-1 negatively regulates several important pathways, such as the transforming growth factorb/bone morphogenetic protein, Wnt/ b-catenin and PI3K/protein kinase B signalling pathways. 16,[26][27][28] However it is not clear whether CKIP-1 is related to the Ras/ERK signalling pathway. To clarify this, the current study measured the protein levels of Ras and ERK1/2 in CKIP-1 shRNA and overexpressed SGC7901 cells.…”
Section: Discussionmentioning
confidence: 99%